2013
DOI: 10.1093/nar/gkt986
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of the C-terminal half of the Saccharomyces cerevisiae Rad52 protein

Abstract: The Saccharomyces cerevisiae Rad52 protein is essential for efficient homologous recombination (HR). An important role of Rad52 in HR is the loading of Rad51 onto replication protein A-coated single-stranded DNA (ssDNA), which is referred to as the recombination mediator activity. In vitro, Rad52 displays additional activities, including self-association, DNA binding and ssDNA annealing. Although Rad52 has been a subject of extensive genetic, biochemical and structural studies, the mechanisms by which these ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…For further clarification, we used anti-Rad51 antibody–protein A agarose to test whether E. coli DNA ligase co-precipitated with Rad51. In a positive control, Rad52, which is known to bind Rad51 at specific sites (12,44), was precipitated with Rad51 by the anti-Rad51 antibody-protein A agarose, but E. coli DNA ligase was not precipitated at all under these conditions (Figure 9). These results clearly indicated the absence of physical interactions between Rad51 and E. coli DNA ligase.…”
Section: Resultsmentioning
confidence: 99%
“…For further clarification, we used anti-Rad51 antibody–protein A agarose to test whether E. coli DNA ligase co-precipitated with Rad51. In a positive control, Rad52, which is known to bind Rad51 at specific sites (12,44), was precipitated with Rad51 by the anti-Rad51 antibody-protein A agarose, but E. coli DNA ligase was not precipitated at all under these conditions (Figure 9). These results clearly indicated the absence of physical interactions between Rad51 and E. coli DNA ligase.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal yRad51 binding region of yRad52 is required for mediator activity [ 19 , 26 ]. To investigate whether the same region is involved in the stimulation of DNA strand exchange by hRAD51, we constructed a derivative of yRad52 that lacked the C-terminal region (yRad52NM; Fig 1B and 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this and other structural and biochemical evidence, we propose a model of yRad52-mediated annealing ( Fig 6 ). Crystallography has revealed that N-terminal half of hRAD52 adopts an undecameric ring structure in which the ssDNA binding groove runs around the outside rim of the ring (dashed line in Fig 6A ) [ 22 , 26 , 43 ]. Although the C-terminal region is not included in the crystal structure, we speculate that the C-terminal secondary DNA binding sites of yRad52 (green spheres in Fig 6 ) face to the primary ssDNA binding sites from outside of the ring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast Rad52 (yRad52) is a key HR mediator that plays critical roles in Rad51 loading, DNA binding and single-stranded DNA (ssDNA) annealing during HR events [20]. Based on this mechanism, yRad52 was used to enhance gene targeting efficiency in mammalian cells to increase gene targeting by 37-fold via HR in Hela cells [21].…”
Section: Introductionmentioning
confidence: 99%